2000
DOI: 10.1017/s1041610200006426
|View full text |Cite
|
Sign up to set email alerts
|

Burden in Caregivers of Cognitively Impaired Older Adults Living in the Community: Methodological Issues and Determinants

Abstract: Considerable burden is reported by informal caregivers of older individuals with cognitive impairment. Significant progress in the understanding of determinants of this burden has been achieved. However, further progress could be attained if we considered important methodological issues that may have limited our understanding of caregiver burden. These issues include subgroups of care recipients and caregivers, measurement issues, research design, and statistical techniques. Fifty-three studies published betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
1
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(100 citation statements)
references
References 79 publications
8
84
1
6
Order By: Relevance
“…In this study we only found a weak association between state anxiety and being female. These results partly contradict the results of previous studies, which have reported more distress, depression and anxiety in female than in male carers (27)(28)(29). The three factors, being female, a spousal carer and a geriatric inpatient, explained only 25 % of the variance in the adjusted linear regression analysis.…”
Section: Discussioncontrasting
confidence: 97%
“…In this study we only found a weak association between state anxiety and being female. These results partly contradict the results of previous studies, which have reported more distress, depression and anxiety in female than in male carers (27)(28)(29). The three factors, being female, a spousal carer and a geriatric inpatient, explained only 25 % of the variance in the adjusted linear regression analysis.…”
Section: Discussioncontrasting
confidence: 97%
“…The internal consistency of T-ZBI-12 was identical to that reported by Hebert, who proposed a shorter version based on 12 items and compared it with the original version (10,12). The mean T-ZBI-12 score was also comparable with that reported by other validation studies (11,17). Besides being a short screening tool, T-ZBI-12 gave results similar those of the full version for use in caregivers of AD patients.…”
Section: Discussionsupporting
confidence: 77%
“…There are many ways to measure caregiver burden (8,9). However, the most widely used instrument for the assessment of caregiver burden is the Zarit Caregiver Burden Interview (ZBI) (10,11) owing to its high internal consistency and good test-retest reliability (12).…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that caring can place a significant level of burden on caregivers resulting in poorer physical and psychological wellbeing (Bell, Araki & Neumann, 2001;Gallagher-Thompson & Powers, 1997). This in turn can affect the care they provide, sometimes leading to premature institutionalisation of the person with dementia (PwD) (Bédard, Pedlar, Martin, Malott & Stones, 2000) or even elder abuse (Wolf, 1998).…”
Section: Caregiver Burdenmentioning
confidence: 99%